Study of Annealing Effects on Physical Properties of Transparent Conducting Oxide - MOHAMMAD ROZATI, SEYED; KHOJEH, ABDOLHAMIED (Asian Journal of Chemistry, 2010)
In this work, the annealing effects on transparent conducting oxide thin films prepared using the spray pyrolysis technique on soda-lime glass substrates is reported. The tube-type electric furnace is designed for annealing the films and then annealed the as deposited films in air, nitrogen and vacuum atmospheres. The annealing in air and nitrogen atmospheres was done from temperature range of 100-500ºC for about 1 h. No change was observed on physical properties of the ZnO and ZnO:Al films until 200ºC annealing temperature. With annealing process in nitrogen atmosphere, the sheet resistance of the films decreased up to the annealing temperature of 400ºC and then slightly increased above 500ºC. With annealing in vacuum atmosphere, a further decrease in sheet resistance of the films is observed.